A novel anterior nasal swab to detect respiratory viruses: a prospective study of diagnostic accuracy - Shidan Tosif; Lai-yang Lee; Jill Nguyen; Isabella Overmars; Chris Selman; Anneke C. Grobler; Alissa McMinn; Gregory Waller; Sarah McNab; Tayla Jarvis; Andrew Steer; Franz E. Babl; et al. (BMC Pediatrics, 2023)
Abstract Detection of respiratory viruses requires testing of the upper respiratory tract to obtain specimens for analysis. However, nasal and throat swabs can cause discomfort and procedural anxiety in children. Respiratory sampling methods which are accurate and less invasive are needed. We aim to determine the positive and negative percentage agreement of a novel anterior nasal swab (ANS) compared with the combined throat and anterior nasal swab (CTN), the reference standard, for detection of respiratory viruses. Children 5 – 18 years of age presenting to a tertiary paediatric hospital with respiratory symptoms were tested with both swabs in randomised order. Respiratory samples were tested on a multiplex RT-PCR panel. Viral detections, RT-PCR cycle-threshold values and child/parent/clinician experience of the swab were recorded. There were 157 viral detections from 249 participant CTN swabs. In comparison with the CTN, the overall positive and negative percentage agreement of ANS for detection of respiratory viruses was 96.2% (95% CI, 91.8–98.3%) and 99.8% (95% CI, 99.6–99.9%), respectively. The ANS was “extremely comfortable”, or only a “little uncomfortable” for 90% of children compared with 48% for CTN. 202 children (84%) rated the ANS as the preferred swab, and 208 (87%) indicated they would prefer ANS for future testing. The ANS required additional laboratory handling processes compared to the CTN. The ANS has high positive percentage agreement and is comparable to the current standard of care. The high acceptability from the less invasive ANS provides a more comfortable method for respiratory virus testing in children. Trial registration ClinicalTrials.gov ID NCT05043623.